2021
DOI: 10.1177/1356336x211050922
|View full text |Cite
|
Sign up to set email alerts
|

Investigating preservice classroom teachers’ practices and views about teaching physical education lessons: An exploratory case study

Abstract: Focusing on preservice classroom teachers (PCTs) with a physical education (PE) specialization, this exploratory case study aimed at investigating the teaching quality in the lessons offered by these teachers during their field placement, as well as examining their views about teaching PE. Toward this end, seven volunteer female PCTs studying at a national university in Cyprus were recruited; all had attended three PE specialization courses before their field placement. Data were gathered through systematic ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…First, this study focused on PCTs’ views and experiences about teaching PE instead of their actual teaching. Although a previous study (Tsangaridou et al, 2022) showed the views of the PCTs in the specialization group to be largely aligned with their teaching, caution needs to be taken in considering these results as reflecting actual differences in PCTs’ practice. Second, we recognize that these differences might not be solely due to the specialization route that one of the groups had taken.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…First, this study focused on PCTs’ views and experiences about teaching PE instead of their actual teaching. Although a previous study (Tsangaridou et al, 2022) showed the views of the PCTs in the specialization group to be largely aligned with their teaching, caution needs to be taken in considering these results as reflecting actual differences in PCTs’ practice. Second, we recognize that these differences might not be solely due to the specialization route that one of the groups had taken.…”
Section: Discussionmentioning
confidence: 89%
“…The current research is part of a larger project focusing on the experiences of PCTs learning to teach PE. A previous study explored the teaching quality of the lessons taught by PCTs with a PE specialization (Tsangaridou et al, 2022). By employing a more comparative perspective, this study focuses on the views of two groups of PCTs—one with a PE specialization and one without—to gain insights into their views and experiences during student teaching.…”
Section: Research Purposementioning
confidence: 99%
“…Ayvazo and Ward (2011) studied the content development of two experienced elementary PE teachers based on task adaptations. In another study, Tsangaridou et al (2022a) described the content development of elementary classroom teachers and found that more effective teachers progressively engaged children in informing, refining, extending, and applying tasks. In the same pattern, Gusthart (1985) focused on describing in-service secondary PE teachers’ content development while teaching PE classes.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, most research has been conducted at the elementary and secondary levels, leaving the preschool level largely overlooked. In addition, participants were PE teachers, with the exception of one study in which they were generalist classroom teachers (Tsangaridou et al, 2022a). This suggests that there is still much to know about the content development of preschool teachers in PE.…”
Section: Introductionmentioning
confidence: 99%